Mathematical model estimation of dengue fever transmission risk from Southeast and South Asia into Japan between 2016 and 2018 - Ken Sakamoto; Takenori Yamauchi; Akatsuki Kokaze (Komiyama Printing Co. Ltd, 2023)
Background: Dengue fever is a viral infection transmitted to humans through the bite of a mosquito infected with the dengue virus. Dengue is one of the most common infectious diseases in the world, and its incidence is rapidly increasing. We estimated the risk of dengue importation from endemic countries to Japan and the transmission risk within Japan using data collected between 2016 and 2018. Methods: We conducted simulations that included the number of reported dengue infections and travelers per month in ten countries in Southeast and South Asia. Results: The estimated importation risks for Japanese returnees and international travelers from each of the ten endemic countries was approximately 1.0 every month from 2016 to 2018. The autochthonous transmission risk in Japan from any target country was 1.0 from June to September yearly. The estimated number of Japanese dengue cases returning to Japan is approximately 25 times higher than that of imported cases reported in Japan. Conclusions: The risk of dengue importation into Japan can be sufficiently high. Attention should be paid to autochthonous transmission spread between June and September when mosquitoes are active in Japan. Estimates of seasonal risk variation from each dengue virus-endemic country can be used to inform preventive and control measures for dengue in Japan.